Natural experiments: finding answers to important questions (Nobel Prize 2021) - Shymanska, Oksana (Herald of Economics, 2022)
Introduction. The importance of using natural experiments in economic research has been repeatedly proven by scientists. However, only in recent years have natural experiments become an integral part of the analytical toolkit of economists through the efforts of A. Meyer, T. Peters, A. Krueger and other scientists. Natural experiments can pose a serious challenge to the established findings of economic theory, as evidenced by the research of David Card, Joshua Angrist and Guido Imbens – winners of the Nobel Prize in Economics 2021.Prupose. Justify the contribution of the Nobel Laureates in Economics 2021 in the development of economics by clarifying the specifics and role of their natural experiments in order to explain the causal relationships in economic phenomena and processes.Methods. During the preparation of the paper general scientific research methods were used: analysis, synthesis, induction, deduction, graphic method, which contributed to the substantiation of specific analytical toolkit of scientific research used by D. Card, J. Angrist and G. Imbens to identify causal relationships in economic phenomena and processes related to the functioning of labor markets, studying the impact of immigration, education, future income, etc.Results. The research awarded the Nobel Prize in Economics 2021 «for empirical contribution to the labor economy» (D. Card) and «methodological contribution to the analysis of causation» (J. Angrist, G. Imbens), first of all prove the fact the ubiquity of natural experiments, the only problem is to be able to find appropriate conditions for their realization. In particular, the researchers announce that changes in policy that take place in one region but not in another, tax breaks, differences in enrollment of children in schools, duration of study, etc. – these are random events that are unaffected (any artificial intervention) divide people into groups: those to whom changes are applied and those who do not experience them (so-called control groups). In particular, J. Angrist and G. Imbens during a natural experiment found that those who study longer earn more in the future: an additional year of study for a person is affected by an average increase in his earnings by 9%. D. Card, conducting another natural experiment, not only did not confirm, but to some extent refuted the established conclusion of economic theory that there is an inverse causal relationships between the growth of the minimum wage and employment in the labor market. The increase in the minimum wage, according to the results of the experiment, had a positive effect on employment in the segment of low-skilled labor. Examining the problems of immigration, the scientist proved that the economic consequences of entering the country of new migrants are minimal. Nobel Laureates 2021 have «revolutionized» empirical research in the social sciences, significantly increasing the ability to find answers to current economic questions, to identify more reliable causal relationships with fundamentally different research toolkit, such as natural experiments.Discussion. Although causal relationships in natural experiments are difficult to determine, this does not detract from the importance of the results. If the quality of the evidence obtained confirms the certainty effect or indicated intervention in a natural experiment, scientists and those who are making responsible decisions should analyze best use evidence to implement promising practices in economic and social spheres of human life. In order to increase the role of natural experiments in the future, it is important to identify those areas of their application in which the evaluation of the results of natural experiments is of the greatest value. Constructing the «design» of a new natural experiment before its implementation, requires the cooperation of those who will later make appropriate decisions with researchers to develop appropriate methodologies, identify existing data, develop a mechanism for collecting new data to ensure the reliability of future natural experiments and adequacy identified causal relationships in the studied phenomena. The demand for evidence of the real qualitative impact of various programs and policies is growing and will continue to grow, which will require stakeholders and researchers for better understanding the benefits and possibilities of applying the results of natural experiments.